Unravelling the innovation puzzle: The interplay between uncertainty, economic institutions, and innovation performance in advanced and developing economies - Kafka, Kyriaki I.; Kostis, Pantelis C. (Technological Forecasting and Social Change, 2024)
Uncertainty profoundly shapes modern production models and the institutional framework of economies. This study investigates the assumption that heightened uncertainty leads to reduced innovation outcomes. Using an unbalanced panel dataset of 143 countries from 1997 to 2020, the analysis reveals that increased uncertainty significantly affects economies' innovation performance. Economic institutions play a critical role in this process, acting as safeguards or enhancers under high uncertainty. Uncertainty and economic institutions work in synergy, with uncertainty exerting a more prominent impact. In advanced economies, uncertainty and economic institutions negatively influence innovation outcomes, but these economies counteract uncertainty by increasing research and development (R&D) spending. Economic institutions may limit R&D expenditure but create an environment conducive to higher researcher employment. On the other hand, developing economies experience a stronger negative effect of uncertainty compared to advanced economies, and economic institutions require support to foster innovation production. Moreover, these economies have limited capacity to mitigate uncertainty through R&D investments. Overall, this study underscores the complex relationship between uncertainty, economic institutions, and innovation outcomes across different types of economies.
Keywords: Economic activity; Innovation; Institutions; uncertainty; Uncertainty shocks